Wybrane motywy archeologiczne z zakresu archeologii śródziemnomorskiej na monetach europejskich z lat 1990–2005 - Lajsner, Włodzimierz (Folia Praehistorica Posnaniensia, 2023)
The role of coins is not limited only to a means of payment, but through the various iconographic and epigraphic contents they contain, coins are also a means of cultural communication. The obverse and reverse of coins are a specific form of image, which includes motifs understood as a repeating decorative element that is also a pattern or an iconographic element expressing specific symbolism and themes. Archaeological motifs reflect archaeological monuments or their elements, and their themes commemorate not only the monument itself, but also related aspects studied by archaeologists, e.g. the broadly understood context. The aim of the considerations was to examine the numismatic form of commemorating and popularizing archaeological heritage on the example of selected motifs referring to monuments of Mediterranean archeology appearing on European coins in the years 1990–2005. First, the motifs were analyzed in terms of the form of their depiction on coins, then the archaeological theme with which the motifs were connected was determined and, on its basis, axiological considerations were carried out, the aim of which was to learn a potential answer to the question – why a given motif was placed on a coin.